Antipsychotic and benzodiazepine use and brain morphology in schizophrenia and affective psychoses – Systematic reviews and birth cohort study. (30th November 2018) - Huhtaniska, Sanna; Korkala, Iikka; Heikka, Tuomas; Björnholm, Lassi; Lehtiniemi, Heli; Hulkko, Anja P.; Moilanen, Jani; Tohka, Jussi; Manjón, José; Coupé, Pierrick; Kiviniemi, Vesa; Isohanni, Matti; et al.
Highlights: In schizophrenia, higher antipsychotic dose associated with smaller nucleus accumbens. In affective psychoses, higher benzodiazepine dose associated with larger GM volumes. Benzodiazepine use confounded some associations in schizophrenia. Benzodiazepine effects on brain should be investigated further. More studies on medication effects on brain in affective psychoses are needed. Abstract: The aim of this paper was to investigate differences in brain structure volumes between schizophrenia and affective psychoses, and whether cumulative lifetime antipsychotic or benzodiazepine doses relate to brain morphology in these groups. We conducted two systematic reviews on the topic and investigated 44 schizophrenia cases and 19 with affective psychoses from the Northern Finland Birth Cohort 1966. The association between lifetime antipsychotic and benzodiazepine dose and brain MRI scans at the age of 43 was investigated using linear regression. Intracranial volume, sex, illness severity, and antipsychotic/benzodiazepine doses were used as covariates. There were no differences between the groups in brain structure volumes. In schizophrenia, after adjusting for benzodiazepine dose and symptoms, a negative association between lifetime antipsychotic dose and the nucleus accumbens volume remained. In affective psychoses, higher lifetime benzodiazepine dose associated with larger volumes of total gray matter and hippocampal volume after controlling for antipsychotic use and symptoms. It seems that in addition to antipsychotics, the severity of symptoms and benzodiazepine dose are also associated with brain structure volumes. These results suggest, that benzodiazepine effects should also be investigated also independently and not only as a confounder.